Effectiveness Of Reception Services For North Maluku Regional Police Police Post Moving To Sofifi City - Wahyudi, Dodi Tri; Kader, Abdurrahman; Hafel, Muhlis (SEAN Institute, 2024)
The move of the North Maluku Regional Police from Ternate City to Sofifi City is a significant change that has an impact on the National Police NCO recruitment service. The background to this research is based on the need to understand how moving locations affects the effectiveness of police services. The aim of this research is to evaluate the impact of the North Maluku Regional Police's move to Sofifi City on the National Police NCO recruitment service. This research focuses on how displacement affects selection processes, infrastructure, coordination, and responsiveness to community needs. The method used in this research is a qualitative method with a continuous analysis approach. Data was collected through in-depth interviews, field observations, and document analysis. Interviews were conducted with informants who had knowledge of the process of recruiting National Police NCOs and changing Polda locations. Observations were used to assess the condition of facilities and infrastructure at the Sofifi Regional Police Headquarters, while document analysis provided context for the policies and procedures implemented. The research results showed that the move of the North Maluku Regional Police to Sofifi City had an impact on several aspects of the National Police NCO reception service. Limited facilities and infrastructure at the Sofifi Regional Police Headquarters are the main challenges, which affect the efficiency and effectiveness of the selection process. Coordination between the Regional Police in Ternate and Sofifi also showed obstacles, which could cause delays and logistical difficulties. However, this move also offers opportunities for innovation and improvement, with the application of technology and new ideas that can improve the quality of service. In conclusion, to ensure the effectiveness of the National Police NCO recruitment service, efforts are needed to improve facilities, strengthen coordination, and make optimal use of technology . It is hoped that the recommendations from this research will help the North Maluku Regional Police in facing challenges and improving the effectiveness of services after moving to Sofifi City.